Effect of VERO pan‐tilt motion on the dose distribution. (6th June 2017) - Prasetio, Heru; Yohannes, Indra; Bert, Christoph
Abstract: Tumor tracking is an option for intra‐fractional motion management in radiotherapy. The VERO gimbal tracking system creates a unique beam geometry and understanding the effect of the gimbal motion in terms of dose distribution is important to assess the dose deviation from the reference conditions. Beam profiles, output factors (OF) and percentage depth doses (PDD) were measured and evaluated to investigate this effect. In order to find regions affected by the pan‐tilt motion, synthesized 2D dose distributions were generated. An evaluation of the 2D dose distribution with the reference position was done using dose difference criteria 1%–4%. The OF and point dose at central axis were measured and compared with the reference position. Furthermore, the PDDs were measured using a special monitoring approach to filtering inaccurate points during the acquisition. Beam profiles evaluation showed that the effect of pan‐tilt at inline direction was stronger than at the crossline direction. The maximum average deviation of the full width half maximum (FWHM), flatness, symmetry, penumbra left and right were 0.39 ± 0.25 mm, 0.62 ± 0.50%, 0.76 ± 0.59%, 0.22 ± 0.16 mm, and 0.19 ± 0.15 mm respectively. The ÔF and the measured dose average deviation were <0.5%. The mechanical accuracies during the PDD measurements were 0.28 ± 0.09 mm and 0.21 ± 0.09 mm for pan and tilt and pan or tilt position. The PDD average deviations were 0.58 ± 0.26 % and 0.54 ± 0.25 % for pan‐ or‐ tilt and pan‐ and‐ tilt position respectively. All the results showed that the deviation at pan and tilt position are higher than pan or tilt. The most influences were observed for the penumbra region and the shift of radiation beam path.